Pengaruh Perilaku Organisasi Pada Kinerja Pegawai - Reni Ridha Wahyuni; Siswoyo Haryono (Universitas La Tansa Mashiro, 2014)
The purpose of this research was to examine empirically the effect between organizational cultures, discipline and job satisfaction on job performance among the employees at Regional Financial Revenue Management Official in Banten Province. The subjects of this research were 130 employees selected as samples by using proportionate stratified random sampling technique taken from the overall population of 193 employees. The data of each variable were collected separately by the respondents’ filling in a questionnaire. The effect technique was applied to analyze the data which had been previously treated with the regressive and correlation procedure. The result proved that the employees’ job performance was positively affected by the organizational culture, discipline and the job satisfaction in Regional Financial Revenue Management Official in Banten Province, and the job satisfaction was positively affected by the organizational culture, and discipline. The findings suggest that the variation of the job performance of the employees might have been affected by the organizational culture, discipline and the job satisfaction.